A state-of-the-art security and attacks analysis in blockchain applications network. (16th February 2022) - Das, Sunayana; Mohanta, Bhabendu Kumar; Jena, Debasish
In recent years, blockchain has emerged as one of the promising technologies in applications like internet of things, smart city, digital management, healthcare system, supply chain management, real estate business, smart agriculture, smart retail and smart grid. Blockchain is derived from bitcoin cryptocurrency white paper in 2008 where peer to peer transactions are done. Though blockchain is considered a secure platform to store the information in digital ledger format in trustful environment with proper verification and validation process. Distributed architecture of blockchain network required high computation devices for mining and doing the cryptographic operation like digital signature. In a decentralised network challenges such as data validation, transaction integrity, fault tolerance, user anonymity are need to be addressed. In this paper, the state of the art of security attacks and various network architecture challenges are identified. The security attacks in the blockchain are discussed in-depth. The various applications of blockchain and corresponding security challenges are also explained. Lastly, the implementation of blockchain network creation, deployment of smart contracts using the open-source Ethereum platform was demonstrated.